A Lamellar MXene (Ti3C2Tx)/PSS Composite Membrane for Fast and Selective Lithium‐Ion Separation. (7th September 2021) - Lu, Zong; Wu, Ying; Ding, Li; Wei, Yanying; Wang, Haihui
Abstract: A two‐dimensional (2D) laminar membrane with Li + selective transport channels is obtained by stacking MXene nanosheets with the introduction of poly(sodium 4‐styrene sulfonate) (PSS) with active sulfonate sites, which exhibits excellent Li + selectivity from ionic mixture solutions of Na +, K +, and Mg 2+ . The Li + permeation rate through the MXene@PSS composite membrane is as high as 0.08 mol m −2 h −1, while the Li + /Mg 2+, Li + /Na +, and Li + /K + selectivities are 28, 15.5, and 12.7, respectively. Combining the simulation and experimental results, we further confirm that the highly selective rapid transport of partially dehydrated Li + within subnanochannels can be attributed to the precisely controlled interlayer spacing and the relatively weaker ion‐terminal (−SO3 − ) interaction. This study deepens the understanding of ion‐selective permeation in confined channels and provides a general membrane design concept. Abstract : Lamellar MXene (Ti3 C2 T x )@PSS membranes with specific size exclusion and Li + identification property show excellent mono/multi‐valent ions separation performance. Compared with the traditional 2D membranes, the selectivity of Li + /Na +, Li + /K +, and Li + /Mg 2+ through such membranes is five to ten times improved.